Computational Materials Science: Discovering and Accelerating Future Technologies. Issue 3 (1st March 2019) - Tahini, Hassan A.; Tan, Xin; Smith, Sean C.
Abstract: Moving the boundaries of knowledge, scientific research and technologies forward through the field of computational materials science requires a combination of fundamental understanding of materials properties, an appreciation of the limitations with our current approaches, and the ability to embrace new and emergent technologies. This short Essay highlights the works of the authors in the special issue "Computational Materials Design" published in Advanced Theory and Simulations . It emphasises the role that computational materials design plays in rationalizing and guiding experimental efforts in in the fields of catalysis, semiconductors, hydrogels, and solid‐state electrolytes. Increases in computational power together with accurate hybrid functionals within density functional theory are enabling more reliable and trustworthy descriptions of solids for various electronic and optoelectronic applications. Additionally, high‐throughput screening and machine learning are rapidly becoming indispensable tools in computational materials science across diverse applications such as engineering and predicting new catalysts. Such advances are setting the pace for our discovery of new and novel materials of the future.